Mini-Review: Immunogenic epitopes in apolipoprotein B-100 for atheroprotective immunization - Gerdes, Norbert; Klingenberg, Roland; Justus Liebig University Giessen (My University, 2024)
Here, we provide a concise overview of recent developments in the identification of immunogenic epitopes in human apolipoprotein B-100 for immunization against atherosclerotic cardiovascular disease. Major steps forward toward a clinical application of vaccines include the design of humanized mouse models, tetramer-based identification of antigen-specific T cells, and novel analysis tools, such as single-cell RNA sequencing and cytometry by time of flight, to assess temporal and spatial changes in immune cells in atherosclerotic cardiovascular disease.
Keywords: ddc:610